Enhanced oral bioavailability of meptazinol in cirrhosis. Issue 3 (March 1987) - Birnie, G G; Thompson, G G; Murray, T; Watkinson, G; Brodie, M J
Abstract : Kinetic analysis was carried out after single intravenous (25 mg) and oral (200 mg) doses of the novel partial opioid agonist meptazinol (Meptid) in patients with non-cirrhotic liver disease (NCLD) and biopsy proven cirrhosis. Comparison was made with a group of patients with normal hepatic function. Elimination half-lives after the intravenous dose were slightly prolonged in the cirrhotics (n = 10; 4.2 +/- 0.6 h) compared with the control (n = 8; 2.7 +/- 0.2 h: p less than 0.05) and NCLD (n = 8; 3.2 +/- 0.5 h) groups. There was no significant difference in meptazinol plasma clearance between the groups (cirrhotics = 72 +/- 8 l/h; NCLD = 89 +/- 9 l/h; control = 83 +/- 10 l/h). After the oral dose, seven of 15 cirrhotic patients vomited but only one patient in each of the other groups was unable to tolerate the drug (p = 0.06). This may be explained by very much higher peak meptazinol concentrations in the cirrhotic (n = 8; 184 +/- 37 ng/ml, p less than 0.01) and NCLD (n = 8; 131 +/- 38 ng/ml, p less than 0.05) patients than those of the controls (n = 7; 53 +/- 12 ng/ml) reflecting a mean four-fold and two-fold increase in oral bioavailability respectively (cirrhotics: n = 8; 27.9 +/- 5.3%: p less than 0.001; NCLD: n = 7; 13.7 +/- 3.9% p less than 0.05; controls: n = 7; 6.5 +/- 1.3%). There was no evidence of accumulation after chronic dosing with 200 mg meptazinol four times daily for 13 doses in seven control, seven NCLD and six cirrhotic patients. There were no detectable differences in psychomotor function measured objectively using the Leeds Psychomotor Tester of subjectively by linear analogue scoring between the groups in all three parts of the study. The oral use of meptazinol in patients with chronic liver disease is associated more with the development of nausea and vomiting rather than excessive sedation. These data suggest that dosage reduction in cirrhotic patients is advisable particularly if the drug is taken by mouth.